2011
DOI: 10.1017/s0954579411000149
|View full text |Cite
|
Sign up to set email alerts
|

School-based strategies to prevent violence, trauma, and psychopathology: The challenges of going to scale

Abstract: Children's trauma-related mental health problems are widespread, largely untreated and constitute significant barriers to academic achievement and attainment. Translational research has begun to identify school-based interventions to prevent violence, trauma and psychopathology. We describe in detail the findings to date on research evaluating one such intervention, the Reading, Writing, Respect, and Resolution (4Rs) Program. The 4Rs Program has led to modest positive impacts on both classrooms and children af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 24 publications
(31 reference statements)
1
21
0
Order By: Relevance
“…Most studies of implicit theories of change are related to individual changes such as coping with trauma, aging, or growing and developing from youth to adult (Aber, Brown, Jones, Berg, & Torrente, 2011;Collins & Clark, 2013;Finkelstein, Quaranto, & Schwartz, 2014;Freedman et al, 2006). Only recently has research from the area of evaluation and policy on implicit theories of change focused more broadly on organizations and groups (Cavanaugh, Feldman, & Hertzog, 1998;Haselton & Buss, 2009;Ramanath & Ebrahim, 2010).…”
Section: Implicit Theories About How Change Occursmentioning
confidence: 99%
“…Most studies of implicit theories of change are related to individual changes such as coping with trauma, aging, or growing and developing from youth to adult (Aber, Brown, Jones, Berg, & Torrente, 2011;Collins & Clark, 2013;Finkelstein, Quaranto, & Schwartz, 2014;Freedman et al, 2006). Only recently has research from the area of evaluation and policy on implicit theories of change focused more broadly on organizations and groups (Cavanaugh, Feldman, & Hertzog, 1998;Haselton & Buss, 2009;Ramanath & Ebrahim, 2010).…”
Section: Implicit Theories About How Change Occursmentioning
confidence: 99%
“…Most implementation research on the uptake of evidence-based interventions focuses on programs to alter providers' care patterns [4], introduce new school curricula [5], or modify practices in community settings [6]. Those models may differ from worksite dissemination where adoption and implementation is by an organization, and employees are asked to change their own health behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Research has suggested that in the evaluation of preventive interventions, especially those targeting low-income children, it is important to account for the potential pre-intervention confounding variables of child, family, and school demographic characteristics (e.g., Aber et al, 2011; Currie & Thomas, 1995; Hill, Waldfogel, & Brooks-Gunn, 2002; Jones et al, 2011; Love, Chazan-Cohen, Raikes, & Brooks-Gunn, 2013; Magnuson et al, 2007; Raver et al, 2009). These variables, as detailed below, have been taken into account in previous SEL studies as well to address the heterogeneity of students that may distort the relationships between SEL and child outcome measures (CASEL, 2012; Durlak et al, 2011; Jones & Bouffard, 2012; Merrell et al, 2008; Park-Higgerson et al, 2008; SACD Research Consortium, 2010; Wilson et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Universal SEL programs available to all students in a classroom or school have slightly smaller effect sizes (approximately 0.2 to 0.3 of a standard deviation) than those of more targeted programs for high-risk students who are identified by teachers as having substantial problems (effect sizes of approximately 0.5) (Durlak et al, 2011; Jones & Bouffard, 2012). On balance, high-quality evaluations of individual programs that base their work on carefully articulated theories of action that are closely aligned with SEL theory and practice (e.g., PATHS) tend to reveal positive effects on children (e.g., Aber, Brown, Jones, Berg, & Torrente, 2011; Durlak et al, 2011). In contrast, in some other evaluations, the underlying theories or the combinations of SEL activities might be inadequate to alter students’ overall social-emotional outcomes because a subset of students who had developmental deficits may require more targeted and intensive interventions than school-wide programs (CASEL, 2012; SACD Research Consortium, 2010).…”
Section: Sel and Child Developmentmentioning
confidence: 99%